Econometric Evaluation of Impact of Education Quality on Economic Growth in Azerbaijan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article is dedicated to study of the impact of the quality of education on the economic growth in Azerbaijan. The quality index of education has been selected for two levels: a) up to higher education; b) higher school and post higher school. The indicator of average score (if available) that an applicant obtained in the current year on the country in student admission to the higher schools as a quality index of education in the country at the pre-higher education is offered as an alternative to the number of upper grades (10-12) in the secondary education. In the higher and post-higher education level, the number of articles printed on basic science and engineering per million people in Azerbaijan, and indexed on the Web of Science is taken as a quality index of education. Semi-linear type regression equations were made to assess the dependence of the indicators characterizing economic development.